In enigmate : the evolution of a riddlic idea from symphosius to the child ballads - Sebo, Erin Madeleine (Trinity College (Dublin, Ireland). School of English, 2009)
This thesis studies the evolution of a particular riddle complex within the subgenre of the Symphosian Riddle, a development over more than a thousand years in which, I argue, the line of influence is unusually clear. Chapter one is divided into a translation of the Symphosii Scholastici Aenigmata - the first complete translation to appear in English since that of Raymond Ohl in 1928 - and an essay dealing with the problems entailed in translating both Symphosius and riddle texts in general. Thereafter, the thesis traces a progression through four main "texts" which, it agues, mark significant stages in the development of the Symphosian Riddle.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin.